Using Online Technology to Enhance Educational Mobility. - Gyurko, Charlene C.; Ullmann, Jill (Online Journal of Nursing Informatics)
The purpose of this paper is to discuss an innovative online educational program at Purdue University Calumet School of Nursing. Through a grant entitled: The Development of a Dedicated Online Educational Platform for Masters of Science in Nursing Programs at Purdue University Calumet School of Nursing, this program enhanced learning opportunities for graduate students and helped to make graduate education more probable for adult learners. The program was made possible by an Advanced Education Nursing Grant through the Division of Nursing (DN) Bureau of Health Professions (BHPr), Health Resources and Services Administration (HRSA), Department of Health and Human Services (DHHS). The inclusion of key elements to help support and enhance student learning makes this program unique. Internal infrastructure was also revised to support this program.